Research on Characteristics of Rainfall at Zhuzhou Hydrological Station in Xiangjiang River in Recent 60 Years - YANG Fang; YANG Pan; LU Lu; XIONG Yu (Renmin Zhujiang)
Rainfall is the main source of water resources in Xiangjiang River, so the research on its changing trend is of great significance to the development, utilization and rational allocation of water resources. Based on the rainfall series data of Zhuzhou Hydrological Station in Xiangjiang River from 1955 to 2016, this paper analyzes the regional rainfall characteristics by the mathematical statistics, linear trend, 5 year moving average method, Mann-Kendall test, sliding t test and wavelet analysis. The following conclusions are drawn: (1) In the past 60 years, the annual distribution of rainfall at Zhuzhou Hydrological Station in Xiangjiang River was uneven, but in regularity. The annual average rainfall of many years mainly presents the alternating process of high and low, with significant increase trend. (2) Although the average number of rainy days in many years fluctuates, the overall trend is stable. (3) The periodic oscillation of annual average rainfall and annual average rainy days is the strongest in the time scale of about 14 year and 20 year.In a short period of time after 2016, the amount of rainfall and the number of rainy days will decrease relatively, and then increase, which can provide data support for the study of water resources change characteristics, water resources planning and management, waterlogging and drought control, agriculture, animal husbandry and forestry production in Xiangjiang River Basin.